Implementasi Ekstraksi Informasi Dari Abstrak Jurnal Sains Maritim Menggunakan Metode Ruled Based - Iwan Mahendro; Iman Mujiarto (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
Universities certainly have a lot of important documents stored. Documents stored include scientific works in the form of journals. The journal that is kept has an identity so that if needed it will make it easier for people to find it. A library is a place to store scientific work, both in the form of journals and for storing other documents. The problem currently occurring is that there are so many documents or journals stored that it takes a long time for people who want to find information related to journals. The aim of this research is to provide a solution to make it easier for people who want to find information about many journals. The method proposed in this research is to use the information extraction method. Information extraction is the search for structured information such as entities and attributes. The stages carried out start from collecting the dataset which is then carried out preprocessing where this stage takes the form of converting documents with PDF extensions to documents with HTML extension. Apart from that, at this stage data cleaning is also carried out, meaning that at this stage it will be possible to create new paragraphs. Therefore, the new paragraph needs to be removed. Then the next stage is rule-based information extraction based on keywords and rules. The results of this research are that none of the 50 journal abstract documents failed so that the accuracy obtained was 100%. So the information extraction in this research can be used to search for information from journal abstracts.